KI67 EXPRESSION IN PAPILLARY THYROID CANCER - Vela Ilir; Jovev, Sashko; Kondov, Goran; Petrushevska, Gordana; Ridvan Bajrami (SHMSHM / AAMD, 2021)
Papillary thyroid cancer is the most common thyroid cancer and accounts for over 70% of malignant thyroid diseases. In the last few decades the incidence of the papillary thyroid cancer (PTC) has increased worldwide. The aim of the study is to evaluate the Ki67 protein expression in papillary thyroid carcinoma and to correlate with clinicopathological parameters (age, gender, tumor size, vascular invasion, capsule invasion, lymph node metastasis, multifocality). Materials and methods. The study population consists of 47 patients diagnosed with PTC, and benign thyroid changes. After standard surgical procedure formalin fixed paraffin embedded (FFPE) tissue sections for standard histological and immunohistochemically Ki67 analysis were obtained. Results. Out of 47 patients, 24 (51.06%) were diagnosed with papillary thyroid cancer (Ki67expression varies in the range 8.58-5.76%) and 23 (48.94%) were benign changes of the thyroid gland (expression of Ki67 varies in the range 1.61±1.23%). For Z = 5.49 and p <0.001 (p = 0.000) the cancers had significantly higher Ki67 expression than benign tumors. There was no significant variation in Ki67 expression in papillary thyroid carcinoma in comparison to cervical lymph node metastases and tumor position. These parameters vary with tumor size and multifocality. Conclusion. Ki67 is an appropriate biomarker used to distinguish papillary carcinoma from benign thyroid lesions. Ki67 expression was associated with tumor size and multifocality. High expression of Ki67 could be an important indicator for assessing the clinical course and prognosis of the disease itself.
Keywords: papillary thyroid cancer; expression; Ki67